Apostle Paul’s Teaching on the Gifts of the Spirit Based on 1 Corinthians 12– 14:1–25 and Its Application for Believers Today - Luther Lawing; Rinto Panus (CV. Green Publisher Indonesia, 2026)
This research aims to examine the Apostle Paul's teaching on the gift of the Spirit based on 1 Corinthians 12–14:1-25 and apply it to believers today. The research method used was hermeneutics with a grammatical exegesis approach, which includes the analysis of historical and logical contexts, as well as literature studies from various primary and secondary sources. The results of the research show that there are twelve gifts of the Spirit that Paul mentioned, namely: the gifts of speaking with wisdom, speaking with knowledge, faith, healing, performing miracles, prophesying, discerning spirits, speaking in tongues, interpreting in tongues, apostles, prophets, and teachers. The gift of the Spirit is given by the Holy Spirit to every believer for the common good and edification of the body of Christ, not as a measure of personal righteousness. The implementation of the gift of the Spirit for believers today includes: a correct understanding of the meaning of the gift of the Spirit, the application of biblical principles in its use, and the use of the gift to build, counsel, and comfort the congregation. This study recommends that every believer use the gift of the Spirit responsibly, in love, and in accordance with biblical principles, and be able to distinguish between the gift of the Spirit and the deviations that occur in church practice today.